Is presenteeism good or bad? A phenomenological study in schools - Uslukaya, Alper; Demirtaş, Zülfü; Alanoğlu, Müslim (My University, 2022)
The study aims to analyse the phenomenon in a holistic and comprehensive way according to the perceptions of education workers who experience presenteeism more frequently and reveal the relationship of presenteeism with the sociological, psychological, and theological dynamics of Turkish society. The study was conducted with a phenomenological design, one of the qualitative research methods. The study group consists of five teachers and five school administrators working in Elazığ, a province in Türkiye in the 2020-2021 academic year. It was determined that educators can voluntarily decide to work when they are not feeling well due to motivations such as a sense of responsibility, conscience, commitment to work, public service, and religious sensitivity. In addition, some participants stated that due to organisational pressure, economic difficulties, and workload, employees make a forced decision to work when they are not well. Finally, in addition to the negative results of presenteeism, positive results, which are rarely seen in the literature, were also obtained. Therefore, the experience of presenteeism should be evaluated considering its positive and negative effects on organisations and employees. Finally, suggestions were developed to monitor the situation of employees experiencing presenteeism, develop policies regarding this, and prevent them from being forced to work in bad situations they cannot tolerate.
Keywords: Presenteeism; bad presenteeism; good presenteeism; involuntary presenteeism; voluntary presenteeism